Hubungan Internet Addiction dengan Hubungan Interpersonal dan Kecemasan pada Remaja di Mts Persatuan Islam Cianjur - Ernawati Hamidah; Sifa Fauziah; Dhinny Novryanthi (Universitas Malahayati Lampung, 2022)
ABSTRACT The prevalence of internet users among adolescent in Indonesia is increasing, namaley 64% and the number of teenagers who experience internet addiction is causing interpersonal relationship problem and anxiety in adolescents. This study aims to determine the relationship between internet addiction and interpersonal relationship, and anxiety adolescent. This study is a correlation analysis. There are four instruments used, namely the internet addiction test, network relationship inventory, and the revised children manifest anxiety scale (RCMAS). The analysis used is chi square. The results showed that there was a significant relationship between internet addiction and interpersonal relationships. P value 0.05 and there was no relationship between internet addiction and anxiety. P Value 0.05. The results of this study are expected to show a significant relationship between internet internet addiction and interpersonal relationships and anxiety in adolescent. Keywords: Internet Addiction in Adolescents, Interpersonal Relationship, Anxiety ABSTRAK Prevalensi pengguna internet pada remaja di Indonesia semakin meningkat yaitu 64% dan banyaknya remaja yang mengalami Internet addiction sehingga menimbulkan masalah hubungan interpersonal, dan kecemasan pada remaja. Penelitian ini bertujuan untuk mengetahui hubungan antara internet addiction dengan hubungan interpersonal, dan kecemasan pada remaja.Penelitian ini merupakan penelitian analisis korelasi dengan pendekatan cross sectional. Sampel penelitian ini adalah remaja. Instrument yang digunakan ada tiga yaitu internet addiction test, network relationship inventory, dan the revisied children manifest anxiety scale (RCMAS). Analisis yang digunakan adalah chi square. Hasil penelitian adalah adanya hubungan yang bermakna antara internet addiction dengan hubungan interpersonal P value 0,05 dan dan tidak ada hubungan antara internet addiction dengan kecemasan P Value 0,05. Hasil penelitian ini diharapakan dapat menunjukkan adanya hubungan yang bermakna antara internet addiction dengan hubungan interpersonal dan kecemasan pada remaja. Kata Kunci: Internet Addiction pada remaja, Hubungan Interpersonal, Kecemasan